2021
DOI: 10.21203/rs.3.rs-1138573/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Willingness of Malaysian Parents To Vaccinate Their Children Below 12 Years Old Against COVID-19 – A Large Cross-Sectional Study

Abstract: Background:The administration of a new drug such as the COVID-19 vaccine in children could be a major concern for their parents. This study aims to assess the willingness of Malaysian parents to vaccinate their children < 12 years old against COVID-19. Methods:An online cross-sectional study was conducted nationwide in Malaysia from 29th August 2021 to 17th October 2021. Parents with children < 12 years old were recruited by the snowball sampling method. Results:Of the 4,438 survey responses received, 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Based on research by Rumetta et al (2019) Ng et al (2021) found that the common reasons given by parents who do not want to be vaccinated against COVID 19 are uncertainty about new vaccines (96.1%), concerns about vaccine content (93.2%), limited information about the vaccine from the doctors (82.3%), and believed the vaccine was unsafe (79.8%).…”
Section: Introductionmentioning
confidence: 99%
“…Based on research by Rumetta et al (2019) Ng et al (2021) found that the common reasons given by parents who do not want to be vaccinated against COVID 19 are uncertainty about new vaccines (96.1%), concerns about vaccine content (93.2%), limited information about the vaccine from the doctors (82.3%), and believed the vaccine was unsafe (79.8%).…”
Section: Introductionmentioning
confidence: 99%